2021
DOI: 10.18203/2320-1770.ijrcog20212945
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transvaginal ultrasound role in the prediction of adenomyosis: correlation with histopathology

Abstract: Background: Adenomyosis is a common gynecologic disorder that primarily affects women of reproductive age that has reported incidence of 5-70% in surgical and postmortem specimens. The aim of this study was to evaluate the accuracy of various transvaginal sonographic findings in adenomyosis by comparing them with histopathological results and to determine the most valuable sonographic feature in the diagnosis of adenomyosis.Methods: All transvaginal US findings were correlated with those from histologic examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…These values suggest that sonography can be a reliable tool for evaluating adenomyosis, with a relatively high sensitivity for ruling out the condition and a respectable specificity for confirming its presence. This finding is consistent with previous studies that have also reported somewhat similar diagnostic accuracy parameters [14][15][16] . A recent international study by Maudot et al has reported moderate sensitivity as compared to the current study findings.…”
Section: Discussionsupporting
confidence: 93%
“…These values suggest that sonography can be a reliable tool for evaluating adenomyosis, with a relatively high sensitivity for ruling out the condition and a respectable specificity for confirming its presence. This finding is consistent with previous studies that have also reported somewhat similar diagnostic accuracy parameters [14][15][16] . A recent international study by Maudot et al has reported moderate sensitivity as compared to the current study findings.…”
Section: Discussionsupporting
confidence: 93%